1989
DOI: 10.1159/000146712
|View full text |Cite
|
Sign up to set email alerts
|

Erythrophagocytosis in the Caprine Hemal Node

Abstract: Caprine hemal nodes were studied by transmission electron microscopy after glutaraldehyde fixation and epoxy resin embedding. Hemal node macrophages were observed to be engaged in erythrophagocytosis. In the early stages of endocytosis, intact erythrocytes were contained in some of the heterophagic vacuoles of macrophages. Later, granular, electron-dense material appeared on erythrocytes, presumably as a result of lysosomal degradation of their matrices. Subsequently, the matrix fragmented and probably formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
2
9
0
1
Order By: Relevance
“…A few cells were localized in the lymph follicles. This confirms the findings of Ezeasor et al. (1989) in caprine haemal nodes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A few cells were localized in the lymph follicles. This confirms the findings of Ezeasor et al. (1989) in caprine haemal nodes.…”
Section: Discussionsupporting
confidence: 91%
“…(1998) and Cerutti and Guerrero (2001) studied the bovine haemal nodes. The haemal nodes of goat were investigated by Meyer (1917), Ezeasor and Singh (1988) and Ezeasor et al. (1989).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as both the haemal node and spleen tested qRT-PCR-positive for viral RNA in a number of animals, it is possible that the former may express a higher density of homing receptors for dendritic cells, macrophages, and other antigen presenting cells than the spleen or lymph node. Previous studies have reported the important contribution of the haemal node in the immune processes of domestic ruminants (Ezeasor et al, 1989;Zhang et al, 2012). The present data therefore suggest that together with the spleen and lymph node, the haemal node is likely to be an important site for generation of immune responses as well a potential replication site for the BEFV in cattle.…”
Section: Discussionsupporting
confidence: 62%
“…Winqvist (1954), Ceccarelli et al (1986), Cerutti et al (1998), and Cerutti and Guerrero (2001) have studied bovine hemal nodes. The hemal nodes of goats have been documented by Singh (1988, 1990) and Ezeasor et al (1989). Recently, Zidan and Pabst (2004) have described the hemolymph node of the dromedary camel.…”
Section: Introductionmentioning
confidence: 93%